Manajemen Masjid Persis Al-Istiqomah Pada Masa Pandemi Covid 19 Di Desa Muncangela Kab. Kuningan Jawa Barat - Muhammad Azka Maulana; Khaerul Wahidin; Sumarna Sumarna; Wawan Riswandi (AL-MUFASSIR, 2020)
The Covid 19 pandemic that emerged in mid-2019 has forced people to change their mindset and lifestyle to pay more attention to health aspects with the aim of breaking the chain of the spread of Covid 19. The real impact of the Covid 19 pandemic is also very visible in the aspect of mosques as a means of worship for Muslims. The elements of the mosque which consist of Idarah, Imarah and Riayah, one of which is related to management, after the Covid 19 pandemic, many of which are oriented towards health as the main consideration. Mosque management includes: first, physical management which focuses on the physical management of the mosque, second, fuction management which focuses on mosque functions. Various styles of mosques in Indonesia have implemented their respective management, including the Al-Istiqomah Mosque which is located in the Muncangela Village area, Cipicung District, Kuningan Regency, West Java Province. Because this mosque was established under the auspices of the Religious Organization of Persis (Persatuan Islam), this mosque has a distinctive management style in dealing with the Covid 19 pandemic as developed by Persis.